The Efficiency of Manufacturing Sector: Empirical Evidence From Aceh Province Indonesia - Muhammad Nasir; Eva Arafah; Hizir Sofyan (School of Business, IPB University (SB-IPB), 2018)
This paper was aimed to analyze the efficiency of Manufacturing Sector in Province of Aceh – Indonesia. The analysis was conducted using the secondary data on manufacturing sector of Province of Aceh together with the Data Envelopment Analysis (DEA analysis). Based on the research, it was found that the manufacturers that had highest output included those producing Fertilizer, Chemical, and Rubber whereas the manufacturers that had the lowest output included Foods and Tobaccos. This condition was caused by the lower interest of the producers involving in foods and tobaccos products. By using DEA analysis, the efficiency value of each product is varied. Using constant return to scale (CRS) assumption, there are four manufactures that are not efficient, including Foods and Tobaccos, Textile, Animal skin products and shoes, and Fertilizer, Chemical, and Rubber products.Keywords: efficiency, manufacturing sector, data envelopment analysis